Learning Strategies In Reading Used By The Second Year Students Of Sma Muhammadiyah 1 Surakarta - TRIANA , SEPTI (2012)
This research aims to describe the learning strategies used by second year students of SMA Muhammadiyah 1 Surakarta who has high, middle, and low mark in English subject to improve their reading ability. The writer applies a case study as the type of research. She uses interview, documentation, and observation for collecting the data. The data are taken from the subject of the research in the form of field notes, interview, and document. The result of the research shows that the three subjects of this research use metacognitive, cognitive and social/affective strategies based on O